The Functional Strategy of PT. Kereta Api Indonesia (Persero) at UPT (Technical Implementation Unit) Jatinegara Locomotive Depot - Karunia Burhan (Journal of Social Science, 2020)
Developments and changes in the business climate in industry era 4.0 now requires companies to be more careful in making to a decision that is comprehensive which later will underlie keput usan that is strategy . By formulating a strategy means the company has made a formulation of what must be done both at the corporate level (company), business and functional. In this study will be discussed about how the functional level strategy carried out by PT. Kereta Api Indonesia (Persero) / KAI at UPT (Technical Implementation Unit) Jatinegara Locomotive Dipo . UPT (Technical Implementation Unit) Jatinegara locomotive depot, a workshop for its fleet of locomotives busiest in Pul au serve the needs of Java in a series of long distance train relation 1 Jakarta area of operations throughout the regions of oper ation in Java. As a UPT which is very influential on the smooth supply of railroad services , an effective and efficient strategy is certainly needed . In the study, it will simulate the kaizen method in the UPT (Technical Implementation Unit) of the Jatinegara Locomotive Dipo in carrying out its functional strategy by making direct observations and comparing qualitative data from interviews .